Evidence that corticofugal propagation of ALS pathology is not mediated by prion-like mechanism. (May 2021) - Scekic-Zahirovic, Jelena; Fischer, Mathieu; Stuart-Lopez, Geoffrey; Burg, Thibaut; Gilet, Johan; Dirrig-Grosch, Sylvie; Marques, Christine; Birling, Marie-Christine; Kessler, Pascal; Rouaux, Caroline
Graphical abstract: Highlights: Corticospinal neuron degeneration in ALS is cell autonomous. SOD1 G37R excision from corticospinal neurons prevents their degeneration. Corticospinal neuron rescue does not affect motor death, disease onset or duration. SOD1 G37R excision from corticospinal neurons does not mitigate SOD1 spinal pathology. Corticofugal spreading of ALS is unlikely to rely on prion-like propagation of misfolded SOD1 protein. Abstract: Amyotrophic lateral sclerosis (ALS) arises from the combined degeneration of motor neurons (MN) and corticospinal neurons (CSN). Recent clinical and pathological studies suggest that ALS might start in the motor cortex and spread along the corticofugal axonal projections (including the CSN), either via altered cortical excitability and activity or via prion-like propagation of misfolded proteins. Using mouse genetics, we recently provided the first experimental arguments in favour of the corticofugal hypothesis, but the mechanism of propagation remained an open question. To gain insight into this matter, we tested here the possibility that the toxicity of the corticofugal projection neurons (CFuPN) to their targets could be mediated by their cell autonomous-expression of an ALS causing transgene and possible diffusion of toxic misfolded proteins to their spinal targets. We generated a Crym-CreER T2 mouse line to ablate the SOD1 G37R transgene selectively in CFuPN. This was sufficient to fully rescue the CSN and to limit spasticity, but had no effect on the burden of misfolded SOD1 protein in the spinal cord, MN survival, disease onset and progression. The data thus indicate that in ALS corticofugal propagation is likely not mediated by prion-like mechanisms, but could possibly rather rely on cortical hyperexcitability.